2020
DOI: 10.1016/j.sdentj.2019.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different remineralizing agents on the initial carious lesions – A comparative study

Abstract: Objectives This study aimed to assess and compare the effectiveness of three different remineralizing agents (Tricalcium phosphate paste, Fluoride varnish, and Nano-hydroxyapatite gel) using the DIAGNOdent device. Material and Methods The present clinical study was carried out on 90 initial carious lesions detected by ICDAS caries diagnostic criteria and then take the baseline record by DIAGNOdent device. The selected initial carious lesions were randomly classified int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 15 publications
0
32
0
4
Order By: Relevance
“…32,33 A clinical trial proved that n-HAP, fTCP and fluor varnish exhibited significant remineralising effects on early caries with n-HAP use having the best effect. 34 Another nanotechnology is nanosilver fluorine (NSF), which contains silver nanoparticles, chitosan and fluor. Dentifrice containing NSF has a bacteriostatic effect and exhibits a remineralising effect like NaF.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 A clinical trial proved that n-HAP, fTCP and fluor varnish exhibited significant remineralising effects on early caries with n-HAP use having the best effect. 34 Another nanotechnology is nanosilver fluorine (NSF), which contains silver nanoparticles, chitosan and fluor. Dentifrice containing NSF has a bacteriostatic effect and exhibits a remineralising effect like NaF.…”
Section: Discussionmentioning
confidence: 99%
“…Another clinical study performed by Alhamed et al (2020) on 90 carious lesions (incipient phase) assessed and compared the effectiveness of three different remineralizing agents (Tricalcium phosphate paste, Fluoride varnish, and Nano-hydroxyapatite gel) using a DIAGNOdent device. The authors concluded that all three remineralizing agents were effective in the treatment of initial carious lesion, while the most effective remineralizing agent was nano-hydroxyapatite [91].…”
Section: Hydroxyapatite Nanoparticles In Prophylactic and Regenerative Dentistrymentioning
confidence: 99%
“…Additional experiments were conducted to test the influences on tooth hardness and the remineralization effect using 3% nanosized sodium tri-metaphosphate infused toothpaste [58]. The remineralization effect pertains to the prevention of a caries progressing into a cavity, which is a later stage [59]. It was found that the addition of nanosized sodium tri-metaphosphate had significant influences on both tooth hardness and remineralization.…”
Section: Nanomaterials Toothpastesmentioning
confidence: 99%